Shuttle views the Earth : geology from space - Francis, Peter, 1944-1999; Jones, Pat, 1948 October 19- (Planetary Image Center/Lunar and Planetary Institute, 1985)
LPI slide set converted to a PowerPoint set by the staff of the Spacecraft Planetary Imaging Facility, Cornell University Geological features on Earth photographed by shuttle astronauts. compiled by Peter Francis and Pat Jones Dune Fields, Namibian Coastal Desert -- Sossus Vlei, Namibia -- Tifernine Dune Field, Algeria, Sahara -- Dunes of Simpson Desert, Australia -- Dust Storm in Progress, Mauritania -- Dust Storm in Progress, Cerro Galan, Argentina -- Oblique View, Galapagos Islands, Pacific Ocean -- Tahaa, Raiatea, Bora Bora, and Tupai Atolls, Pacific Ocean -- Canton Atoll, Phoenix Islands, Pacific Ocean -- Great Barrier Reef, East Coast of Australia -- Eleuthera Island, Exuma Sound, Bahamas -- Sand Spit, Baia de Sepetiba, Brazil -- Richat Structure, Ouadane, Mauritania -- Ring Intrusion, Jebel Uwaynat, Sudan/Egypt/Libya -- Brandberg Intrusion, Namibia -- Granitic Intrusion, Chanaral, Chile -- Gosses Bluff Meteorite Crater, Australia -- Manicouagan Impact Crater, Quebec, Canada -- Anticlines and Salt Domes, Gulf Coast, Iran -- Aswan Dam, Lake Nasser, and Nile River, Egypt -- Dendritic Drainage Pattern, Yemen -- Peneplain Cut by Canyons, Andean Slopes, Peru -- Sediment Laden Drainages, Betsiboka River, Madagascar -- Superimposed Drainages, Macdonnell Ranges, Australia -- Oblique View, Sinai Peninsula, Egypt -- Uplifted Basalt Plateau, Somalia Coast -- Atacama Fault, Chile Coast, South of Antofagasta -- Great Dike, Zimbabwe, Africa -- Folds in Basement Rocks, Flinders Range, Australia -- Folds in Metasediments, Belcher Islands, Canada -- Glaciers, Lakes, and Fault Zone, Tibet Plateau -- Carachipampa Volcano and Red Beds, N.W. Argentina -- Coast and Andes Mountains, Chile -- Dacite Domes and Ignimbrites, Sud Lipez, Bolivia -- Massive Volcanic Debris Avalanche, Socompa Volcano, Chile -- Debris Avalanche Deposit, Tata Sabaya, Bolivia -- Pico de Teide, Tenerife -- Eruption Plume, Masaya Volcano, Nicaragua -- Gorelyy Krehbet Volcano, Kamchatka, Russia -- Aniachak Volcano and Surprise Lake, Alaska, USA.